IDIOMATIC EXPRESSIONS FOUND IN THE VLOG VIDEO BY SACHA STEVENSON - Viona Azzhani; Fitri Palupi Kusumawati; Aulia Hanifah Qomar (Journal of English Education and Entrepreneurship (JEEP), 2025)
The objectives of this research are to find out the types of idiomatic expressions, describe the meaning of idiomatic expressions, and find out the strategies used in translating idiomatic expressions. Subject This research is a video vlog script by Sacha Stevenson. The research method used in this research is descriptive qualitative. The results of the research were in the form of 6 types of idioms and 4 idiomatic translations strategies in idiomatic expressions vlog videos by idiom Sacha Stevenson. The idiomatic expression types there are 1 Similes, 1 Binomials, 2 Proverbs, 5 Euphemisms, 8 Clichés and 15 Fixed Statements. The idiomatic translations strategies there are 14 Similar Meanings and Forms, 3 Similar Meanings but Different Forms, 6 Translations by Paraphrasing and 9 Last Translations by Omissions. Based on the data, the researcher concluded that the 6 types of idioms and 4 idiomatic translation strategies in this video, all of them are found in this vlog video.